Analisis Fikih Muamalah terhadap Sistem Pengupahan Freelance “X” Wedding dan Event Organizer - Muhamad Farid Solehudin; Encep Abdul Rojak; Akhmad Yusup (UNISBA Press, 2023)
Abstract. Service work in muamalah fiqh is included in the Ijarah Al-amal contract, in which the provisions must determine how much nominal wages will be given to workers. However, in